The Microphthalmia-Associated Transcription Factor p.E318K Mutation Does Not Play a Major Role in Sporadic Renal Cell Tumors from Caucasian Patients - Stoehr, Christine G.; Walter, Bernhard; Denzinger, Stefan; Ghiorzo, Paola; Sturm, Richard A.; Hinze, Raoul; Moch, Holger; Junker, Kerstin; Hartmann, Arndt; Stoehr, Robert (Pathobiology, 2016)
The transcription factor MITF (microphthalmia-associated transcription factor) is known to induce expression of hypoxia-inducible factor (HIF1-?), which is involved in renal carcinogenesis. The MITF p.E318K mutation leads to deficient SUMOylation of MITF, resulting in enhanced activation of its target genes. A case-control study on melanoma patients who coincidentally were affected by renal cell carcinoma (RCC) has revealed an elevated risk for mutation carriers to be affected by one or both of these malignancies, suggesting a possible role for MITF p.E318K in renal carcinogenesis. The same study described an MITF mutation frequency of 1.5% in a small cohort of sporadic RCC, but comprehensive data on sporadic renal cell tumors are missing. We therefore tested a large cohort of sporadic renal tumors for MITF p.E318K mutation status.Genomic DNA was extracted from 426 formalin-fixed, paraffin-embedded sporadic renal tumors that had been graded according to the 2004 WHO classification of renal tumors and staged according to the 2002 TNM classification. The tumor cohort was enriched with papillary and chromophobe RCC, and also contained benign oncocytomas. DNA was tested for MITF p.E318K by pyrosequencing.Of 403 analyzable tumors, 402 renal tumors were wild-type ones, and only 1 case showed the MITF p.E318K mutation. This tumor was a clear-cell RCC (pT3b N0 M0 G3 according to the TNM classification 2002). The affected patient was male, 61 years old, and had no known coexisting malignancies.The MITF p.E318K mutation does not appear to play a major role in sporadic RCC carcinogenesis, but is possibly restricted to a rare subpopulation of inherited RCC. © 2016 S. Karger AG, Basel.
EVALuna2:6789